2001
DOI: 10.1097/00005344-200107000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Nonselective Endothelin Receptor Antagonist Initiated Soon After the Onset of Myocardial Infarction May Deteriorate 24-Hour Survival

Abstract: To investigate the effects of endothelin blockade initiated immediately after the onset of myocardial infarction on survival and left ventricular remodeling, treatment with the nonselective receptor antagonist TAK-044 (n = 22) or saline (n = 19) for 3 weeks was initiated immediately after coronary ligation in rats. The 24-h survival rate was significantly lower in the TAK-044 group than in the saline group. The systolic blood pressure 24 h after the onset of myocardial infarction was similar in the saline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…19 Indeed, early administration of endothelin antagonists after experimental myocardial infarction may increase mortality, most likely due to a remodelling-related increase in cardiac dimensions. 20 21 …”
Section: Why Did the Clinical Trials Yield Negative Results?mentioning
confidence: 99%
“…19 Indeed, early administration of endothelin antagonists after experimental myocardial infarction may increase mortality, most likely due to a remodelling-related increase in cardiac dimensions. 20 21 …”
Section: Why Did the Clinical Trials Yield Negative Results?mentioning
confidence: 99%
“…Several in vivo studies using ET-receptor antagonists implicated a role for ET in modulating extracellular matrix turnover, tissue repair, and remodeling (7,8,11,16,19,21,22,27,30,39). ET-1 production in the failing heart as examined immunohistochemically revealed heavy ET-1 immunostaining that was confined to granulation tissue and proliferating fibroblasts (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies support the concept that administration of ET antagonists mitigates ET-mediated adverse remodeling (27,30), some reports demonstrate that antagonizing ET action may aggravate remodeling after MI (7). However, the time of treatment with these receptor antagonists and the choice of antagonist used have been shown to play important roles in alleviating the ET-induced adverse remodeling (19,22,29,39). In rats, subsequent to MI, ET was elevated in plasma and heart interstitial fluid (3,8).…”
mentioning
confidence: 99%
“…Thus, factors such as receptor specificity of the drug or time of onset of therapy might influence the outcomes. Studies of endothelin antagonists post-MI have shown beneficial [41,42] and deleterious [43][44][45] results. However, these studies have been of nonselective and selective agents, have started the medications at various times after the infarct, and have treated for various durations.…”
Section: Endothelin Receptor Antagonistsmentioning
confidence: 99%